The Influence Of Human Resource Development On Employee Performance In The Business Support Section Of PT Sucofindo Medan Branch - Weny Rivanka; Nuri Aslami (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In life in the world of work there are bound to be things that contradict employees' performance of their work. Of course, there are still odd things found while working that do not immediately support the values of a job, with this, human resources have a very important role and need to be given serious attention. Employees or employees are human resources who are very vital in improving the performance or even progress of an organization. This research was conducted with the aim of finding out the extent of the influence of human resource development on employee performance in the business support section of PT Sucofindo Medan Branch. The results of research carried out in the business support section of PT Sucofindo Medan Branch, which used an interview method with office employees, the researchers obtained results, which turned out to be by all means and development of human resources in this office such as training, evaluating and improving performance makes human resources in this office better. By using qualitative methods through interview techniques with employees in the business support section of PT Sucofindo Medan Branch, it is hoped that the data received will be data that can be trusted and has good value. Apart from that, the researcher also refined it by looking for several references from previous studies so that the content of the results produced would be even better. Keywords: ,